2008
DOI: 10.1371/journal.pone.0002568
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli Consumption Interacts with GSTM1 to Perturb Oncogenic Signalling Pathways in the Prostate

Abstract: BackgroundEpidemiological studies suggest that people who consume more than one portion of cruciferous vegetables per week are at lower risk of both the incidence of prostate cancer and of developing aggressive prostate cancer but there is little understanding of the underlying mechanisms. In this study, we quantify and interpret changes in global gene expression patterns in the human prostate gland before, during and after a 12 month broccoli-rich diet.Methods and FindingsVolunteers were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 47 publications
4
136
0
1
Order By: Relevance
“…Furthermore, it shows that this reaction must be favorable in biological systems. Modification of amines by isothiocyanates has been previously observed on the N-terminal glycine and phenylalanine residues in insulin, the N-terminal aspartic acid residue in epidermal growth factor (26), and a lysine residue in the transient receptor potential-A1 channel (49). However, modification of amines has not previously been shown to occur either in cells or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it shows that this reaction must be favorable in biological systems. Modification of amines by isothiocyanates has been previously observed on the N-terminal glycine and phenylalanine residues in insulin, the N-terminal aspartic acid residue in epidermal growth factor (26), and a lysine residue in the transient receptor potential-A1 channel (49). However, modification of amines has not previously been shown to occur either in cells or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic regulation could be the key factor, as GSTP1 and GSTM1 hypermethylation and HDACs are prominently involved in prostate carcinogenesis and it has been shown that sulforaphane suppresses both of these mechanisms (24,25,37). These questions will be explored in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, consumption of a known amount of the phytonutrient sulforaphane does not guarantee absorption of a predicted amount of anti-cancer molecule since differences in the glutathione S transferase M1 gene influences the metabolic rate of sulforaphane, a phytonutrient present in broccoli. The faster it is metabolized, the faster it is expelled from the body , Gasper et al 2005, Gross-Steinmeyer et al 2010, Joseph et al 2004, Lampe 2007, Lampe 2009, McWalter et al 2004, Riedl, Saxon and Diaz-Sanchez 2009, Ritz, Wan and Diaz-Sanchez 2007, Traka et al 2008. Similarly, a number of the nutrients, e.g.…”
Section: Dietmentioning
confidence: 99%